(untitled) (Palestine Technical College Journal for Research and Studies, 2023)
The study aims to identify the role of secondary school principals in promoting social peace and their relationship to the culture of tolerance among students from the teachers point of view’ The researcher uses the descriptive analytical method .approach in its analytical style. The study population consists of secondary school teachers in the schools of the governorates of the Gaza Strip, amounting to (3848) male and female teachers, and the study sample amounted to (385) male and female teachers. The researcher built the study tool (the questionnaire). The study found the following results: The role of secondary school principals in promoting social peace reached (72.39%), where it came after sound management in the first place with a relative weight (72.25%), followed by teamwork with a relative weight (71.17%), and then freedom of expression with a relative weight (70.17%).It shows that the relative weight of the axis of tolerance culture reached (73.76%), meaning that it is high, where social tolerance came in the first place with a relative weight (75.36%), followed by religious tolerance with a relative weight (74.9%), followed by intellectual and cultural tolerance with a relative weight (73.29%), followed by Scientific tolerance with a relative weight (71.51%).In light of the results, the researcher recommended the following: Deepening community networking to develop an appropriate methodology for a culture of social peace and supporting and strengthening it in primary schools, raising the level of its activation in secondary schools, activating programs, initiatives and activities to enhance community awareness of the importance of social peace and promoting a culture of tolerance at all schools and their levels.